Design, Rapid Prototyping, and Testing of the Darrieus Wind Turbine - Nik Mohd Faizal Bin Nik Abd Ghani, Nik Mohd Faizal (Universiti Teknologi Petronas, 2009)
This report contains design, rapid prototyping and testing of the Darrieus wind turbine. The Darrieus wind turbine rotates in the same sense regardless of the direction of the air stream. In order to maximize its efficiency, several variations of this turbine design will be required for testing and evaluation. One of the objectives of this project is to test parameters that will affect the performance of the Darrieus wind turbine. Two parameters that will evaluated for evaluation is number of blades of the turbine and diameter of the turbine. Also for each turbine, the minimum wind speed required to start the rotation and the speed it can rotate with varying wind speed will be determined. Three prototypes are created for testing purposes. Results showed that the increase the diameter of the turbine will reduce the rotation of the turbine. In addition higher number of blades will increase the rotation of the wind turbine.